Pengaruh Online Customer Review, Kepercayaan Dan Ketersediaan Produk Terhadap Keputusan Pembelian Ms Glow Di Kota Batam - Desri Yeni Sinaga; Inda Sukati (Komunitas Dosen Indonesia, 2023)
As of Today, technological developments have included buying and selling activities which result in buyers having to pay attention to several aspects before, namely by paying attention to customer reviews, because it is difficult to build trust in making purchases without face to face, with the variety and availability of products increasing the options of buyers, may or may not improve purchasing decisions especially purchases made at Ms Glow Batam. This research is a quantitative study with a population of buyers who make purchases at Ms Glow, a sample of 283 samples. This research concludes that Online Customer Reviews have an effect on Purchasing Decisions, Trust has an effect on Purchasing Decisions, no effect has been found on Product Availability on purchasing decisions, and Online Customer Reviews, Trust, Product Availability have a simultaneous and significant effect on the Purchase Decision of MS Glow in Batam City. The adjusted R square is 0.66 or 65.8%. This value shows how well the independent variable can explain the dependent variable, which is 65.8% with other factors, the remaining 34.2% is influenced by other variables.